Influence of kinematic parameters on ball velocity of the handball penalty throw - Markovic, S.; Markovic, K. (Book of Proceedings Fis Communications 2019, 2019)
The aim of this study was to investigate the influence of some kinematics parameters (upper extremity, trunk position) on ball velocity of the handball penalty throw. Thirty female elite handball players (height: 1.73 +/- 0.08 m; mass: 69 +/- 8.9 kg; BMI 22.9 +/- 2; training experience: 12.3 +/- 6.2 yrs), playing in the first Serbian Handball League from two different clubs volunteered to participate in the present study. The research was of transversal character, during the competition period. An angle of upper body relative to the ground (deg); Shoulder internal rotation (deg); Elbow flexion (deg), that is, the angle closing the longitudinal axis of the upper arm with the longitudinal axis of the forearm was analyzed by Kinovea 0.8.2 kinematic analysis software. Pearson linear correlations were used to calculate the influence of kinematic parameters to throwing ball velocity. A strong negative correlation was calculated between the angle of upper body relative to the ground with the throwing ball velocity (r= -0,496) whereby the big angles relative to the ground was followed by the reduction throwing ball velocity. It has been proven existence of the mean negative correlation between variables shoulder internal rotation and the throwing ball velocity (r= -0,299). Between variables the elbow flexion and the throwing ball velocity there was mean positive correlation (r=0,402), which means that by increasing the angle of elbow flexion increases ball velocity. It can be concluded that the tested kinematic parameters have an influence on the throwing ball velocity in performing a penalty throw in team handball.